2012
DOI: 10.3892/ol.2012.628
|View full text |Cite
|
Sign up to set email alerts
|

The pathobiological features of gastrointestinal cancers (Review)

Abstract: Abstract. Gastrointestinal adenocarcinoma (GIA) is a common malignant disease worldwide. Its tumorigenesis and progression is a multistage process with the involvement of a multifactorial etiology. Knowledge regarding altered expression of these genes during carcinogenesis may not only provide information about the molecular events during the initiation and progression of cancer, but may also result in the discovery of biological markers for the evaluation of cancer diagnosis and prognosis. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Multifactorial mechanisms for network formation result in tumorigenesis in cancers and sarcoma by the activation or deactivation of signaling pathways (5,6). In the present study, the pathology indicated a change from moderately-differentiated adenocarcinoma to poorly-differentiated adenocarcinoma, and to undifferentiated small cell carcinoma.…”
Section: Discussionsupporting
confidence: 46%
“…Multifactorial mechanisms for network formation result in tumorigenesis in cancers and sarcoma by the activation or deactivation of signaling pathways (5,6). In the present study, the pathology indicated a change from moderately-differentiated adenocarcinoma to poorly-differentiated adenocarcinoma, and to undifferentiated small cell carcinoma.…”
Section: Discussionsupporting
confidence: 46%
“…Currently, systemic chemotherapy is the primary means for treatment of advanced gastric cancer, but generated resistance is a major cause of chemotherapy failure. The initiation and progression of gastric cancer is a complex process that involves both genetic and environmental factors (Ludwig and Weinstein, 2005;Yang et al, 2012). Therefore, identification of genetic biomarkers that can predict the prognosis for gastric cancer patients would greatly improve individualized therapy, post-operational treatment, and follow-up strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A critical step in this process is the outgrowth of endothelial cells from preexisting capillary vessels and their migration toward the tumor cells under the stimulation of angiogenic growth factors. 28,29 Circulating endothelial progenitor cells have been found to play a crucial role in sustaining angiogenesis in both primary and metastatic tumors, 30 and high levels of angiogenic factor production have been associated with advanced tumor staging and poor prognosis. [31][32][33] Vascular endothelial growth factor (VEGF)-A has been identified as the key mediator of tumor-associated angiogenesis; thus, it is the most well-characterized and is the key target in antiangiogenic therapy.…”
Section: Introductionmentioning
confidence: 99%